Optimization of a Fe–N–C electrocatalyst supported on mesoporous carbon functionalized with polypyrrole for oxygen reduction reaction under both alkaline and acidic conditions - Osmieri, Luigi; Monteverde Videla, Alessandro H.A.; Specchia, Stefania (International journal of hydrogen energy, 2016)
A series of Fe–N–C non-noble metal electrocatalysts for oxygen reduction reaction (ORR) are synthesized using mesoporous carbon (MPC) as C source, polypyrrole (PPY) as N source and Fe(II) acetate as Fe source. In the first part, the effects of the addition of polyvinylpyrrolidone (PVP) and performing a heat treatment on the MPC-PPY support before the impregnation with Fe2+ ions are investigated. In the second part, the best catalyst obtained in the first part is used as a support, and the influence of a second pyrolysis treatment performed with or without further impregnation with Fe2+ is investigated. The materials are characterized by FESEM, TEM, EDX, BET-porosimetry, XPS, and FTIR. The electroactivity towards ORR is assessed with a rotating disk electrode (RDE) apparatus in both acidic and alkaline conditions. The different synthesis pathways examined have a direct influence on the ORR activity. The electroactivity and micropores content increases after the second heat treatment. [Display omitted] •Fe–N–C catalyst done with mesoporous carbon, polypyrrole and Fe acetate.•Two pyrolysis steps at 800 °C are beneficial for ORR activity.•Formation of a carbon structure containing both carbon nanotubes and graphene.•ORR activity linked to the relative amounts of both pyridinic and pyrrolic nitrogen.•Very high amount of microporous surface area, 50–65% of the total surface area.